2017
DOI: 10.1159/000451066
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors after Curative Resection for Single-Lesion Hepatocellular Carcinoma in Patients with Normal Liver Function: A Historical Cohort Study

Abstract: Background: Hepatic resection for hepatocellular carcinoma (HCC) is now established as the treatment most likely to yield the best outcome. We aimed to clarify the risk factors for HCC recurrence after curative resection of single HCC in patients with normal liver function (NLF). Methods: The clinical records of 105 patients with NFL and a single HCC less than 5 cm in diameter who had undergone curative liver resection between April 2000 and January 2013 were investigated. We analyzed risk factors for recurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Over 50% of patients were disease free at 5 years and over 40% remained disease-free at 10 years. Grazy et al (32) and Shimoda et al (33) reported a comparable DFS for HCC resected patients without cirrhosis and patients with anatomically resected HCC whilst other authors report lower rates ranging from 13-51% (8,34).…”
Section: Discussionmentioning
confidence: 95%
“…Over 50% of patients were disease free at 5 years and over 40% remained disease-free at 10 years. Grazy et al (32) and Shimoda et al (33) reported a comparable DFS for HCC resected patients without cirrhosis and patients with anatomically resected HCC whilst other authors report lower rates ranging from 13-51% (8,34).…”
Section: Discussionmentioning
confidence: 95%
“…Liver subsegmentectomy, proposed by Makuuchi et al , utilizes the portal vein puncture staining method using ultrasound during the operation, and is a method that minimizes the liver resected volume while improving the complete cure rate (2,10,12). This operational method bases its resection region on Couinaud's subsegmentation, has improved the complete cure rate and has reduced post-operative liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 18 ] Many risk factors were associated with the prognosis of patients with HCC after hepatectomy. [ 19 , 20 ] Based on Asian population, researchers had confirmed prognostic factors including AFP levels, vascular invasion, tumor metastases, multiple tumors, and other clinicopathological features. Besides with these factors, many novel biomarkers had been investigated and explored.…”
Section: Discussionmentioning
confidence: 99%